Expression of recombinant Clostridium difficile toxin A and B in Bacillus megaterium - Yang, Guilin (BioMed Central, 2008)
BACKGROUND: Major Clostridium difficile virulence factors are the exotoxins TcdA and TcdB. Due to the large size and poor stability of the proteins, the active recombinant TcdA and TcdB have been difficult to produce. RESULTS: The toxin genes tcdA and tcdB were amplified by PCR using chromosomal DNA from a toxigenic strain as a template, and cloned into a shuttle vector pHis1522. The sequences of both tcdA and tcdB genes in the vector have been verified by DNA sequencing. The constructs were transformed into B. megaterium protoplasts and the protein expression was controlled under a xylose promoter. The recombinant toxins (rTcdA and rTcdB) were purified from bacterial crude extracts. Approximately 5 – 10 mg of highly purified recombinant toxins were obtained from one liter of bacterial culture. The resulting rTcdA and rTcdB had similar molecular masses to the native toxins, and their biological activities were found to be similar to their native counterparts after an extensive examination. CONCLUSION: We have generated the full length and active recombinant TcdA and TcdB in Bacillus megaterium.